A Semiotic Analysis on Leaving Home Short Film - Anjan Hardani, Ni Wayan; Marantika, I Made Yogi (Udayana University, 2025)
This study aims to analyze verbal and non-verbal signs in the short film Leaving Home using semiotic theories by Saussure (1983) and Barthes (1967). A qualitative descriptive method was applied through observation and note-taking to identify and interpret the signs within the short film. The analysis revealed 20 verbal signs and 20 non-verbal signs, classified into seven denotative meanings and thirty-three connotative meanings. The findings indicate that connotative signs are more dominant, highlighting the reliance on implicit representations of the concept of “home.” Verbal and non-verbal elements work together to portray themes of nostalgia, emotional struggle, and identity. This semiotic analysis is an effective approach to uncover layered meanings in short films. The significance of this study lies in its focus on short films a medium less examined in semiotic research while its novelty is shown through exploring how minimal dialogue and visual storytelling construct deep emotional meaning.